ANALISIS KONSUMSI ENERGI LISTRIK PADA PEMBANGUNAN NUWSP BIYONGA KABUPATEN GORONTALO - Boli, Rahmad Hidayat; Pido, Rifaldo; Arbie, Mohamad Rifal; Rauf, Wawan (Jurnal Rekayasa Mesin, 2024)
The need for electrical energy today is starting to increase along with the increase in population and rapid development, but inversely proportional to the progress or innovations in increasing renewable energy. Given that this renewable energy can be developed continuously and operational costs are relatively cheap, the electricity that relies on coal (fossil) over time will run out and cannot be renewed, the discussion concerns the supply of PLN supplies. So that in this study the focus is on the utilization of electrical energy for the NUWSP development area of Gorontalo Regency Biyonga Village and calculating the total consumption needs of the electrical energy used. After research and data analysis, the results obtained are 189 kVA or 189,000 vA, the total peak demand with load is 3 units of centrifugal pumps, 10 points of room lighting, and 12 points of lighting around the building, the results of the analysis obtained became a reference and suggested to install electrical energy with a capacity of 197 kVA or 197,000 vA with the consideration that when development occurs, the demand for electrical energy is still sufficient from what is installed.